COVID-19 Vaccine Acceptability Among Healthcare Facility Workers in Sierra Leone, the Democratic Republic of Congo and Uganda: A Multi-Centre Cross-Sectional Survey - Hilary S. Whitworth; Jonathan Kitonsa; Kambale Kasonia; Kambale Kasonia; Daniel Tindanbil; Daniel Tindanbil; Paddy Kafeero; Joseph Bangura; Joseph Bangura; Yusupha Nije; Yusupha Nije; Darius Tetsa Teta; et al. (Frontiers Media S.A., 2022)
Objectives: This cross-sectional survey explored COVID-19 vaccine acceptability among public healthcare facility workers in Kambia (Sierra Leone), Goma (Democratic Republic of Congo) and Masaka (Uganda).Methods: Questionnaire-based interviews conducted between April-October 2021 explored participants' knowledge and perceptions of, and attitudes towards, the COVID-19 pandemic and COVID-19 vaccines, as well as COVID-19 vaccine acceptability (defined as uptake of ≥1 dose or intent to get vaccinated).Results: Whilst most (n = 444; 81.8%) of the 543 participants had one or more concerns about COVID-19 vaccines, 487 (89.7%) nonetheless perceived that they were important for pandemic control. Most participants from Kambia or Masaka either were vaccinated (n = 137/355; 38.6%) or intended to get vaccinated (n = 211/355; 59.4%) against COVID-19. In Goma, all 188 participants were unvaccinated; only 81 (43.1%) participants intended to get vaccinated, and this was associated with positive perceptions about COVID-19 vaccines. In Goma, the most common reasons for not wanting a COVID-19 vaccine were concerns that the vaccines were new (n = 75/107; 70.1%) and fear of side effects (n = 74/107; 69.2%).Conclusion: Reported COVID-19 vaccine acceptability was high among healthcare facility workers in Kambia and Masaka. The lower vaccine acceptability in Goma may highlight the importance of social mobilisation and accurate, accessible information that addresses specific concerns.